Robust Chronic Kidney Impact Identification System Using Prab Algorithm - Imran, S. Mohammed; Prakash, N.; Hazeena, K.; Sivasubramanian, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Kidneys act as one of the important organs of the body. Kidney disease needs to be treated in the early stages to protect Human life. Chronic kidney disease slowly impacts the functionality of kidneys that make severe damage to kidneys if untreated. Chronic kidney disease affects other organs of the body and creates life threatening problems. Early prediction of kidney disease can save the life of the person and reduce the financial cost taken for treatment purposes. The proposed approach is focused on developing a robust algorithm named probability weighted AdaBoost to predict chronic kidney disease. The adaptive weight calculation of Adaboost algorithm (PRAB) is modified here to provide the reduction of incorrectly classified values on kidney disease detection. The existence of false positive data is one of the major drawbacks produces that induces similarity issues in classification. To avoid the weak classification criteria PRAB algorithm is utilized here. The adaptive selections of classifier with removal of weak data analyzer enhance the accuracy of prediction.